An image encryption scheme based on a hybrid model of DNA computing, chaotic systems and hash functions - Zefreh, Ebrahim Zarei (Multimedia tools and applications, 2020)
In this paper, we propose a novel image encryption scheme based on a hybrid model of DNA computing, chaotic systems and hash functions. The significant advantage of the proposed scheme is high efficiency. The proposed scheme consists of the DNA level permutation and diffusion. In the DNA level permutation, a mapping function based on the logistic map is applied on the DNA image to randomly change the position of elements in the DNA image. In the DNA level diffusion, not only we define two new algebraic DNA operators, called the DNA left-circular shift and DNA right-circular shift, but we also use a variety of DNA operators to diffuse the permutated DNA image with the key DNA image. The experimental results and security analyses indicate that the proposed image encryption scheme not only has good encryption effect and able to resist against the known attacks, but also is sufficiently fast for practical applications. The MATLAB source code of the proposed image encryption scheme is publicly available at the URL: https://github.com/EbrahimZarei64/ImageEncryption .